Sparse Relays Assisted Opportunistic Routing for Data Offloading in Vehicular Networks - Qin, Xu; Huang, Guanglun; Zhang, Baoxian; Li, Cheng (IEEE International Conference on Communications (2003), 2021)
In this paper, we study the design of opportunistic routing for efficient data offloading in vehicular opportunistic networks with the assistance of sparsely deployed static relays. The objective is to maximize the data offloading ratio and also reduce the average delivery delay while respecting the data's delay requirement. For this purpose, we propose a sparse relay assisted opportunistic routing algorithm for efficient data offloading. We show how to efficiently utilize the encounters with static relays for improved data offloading performance based on vehicles' trajectories. We further design a greedy algorithm for optimized relay deployment. We reduce the computational complexity of the data offloading algorithm and also the relay deployment algorithm, respectively. Simulation results demonstrate the high performance of our proposed algorithms.